Phoretic mites (Rhinoseius spp.) in Apodiformes from Cerrado and Pantanal Biomes in midwestern Brazil - Ramos,D. G. S. (2020)
Abstract Nasal mites are commonly found in hummingbirds (Apodiformes). In most cases, endoparasitic mites were reported to parasitize the respiratory system, particularly the anterior nasal chambers, larynx, trachea, lungs, and the air and conjunctival sacs. However, some mites are only carried by hummingbirds, because flowers serving as a nutrient source for these small mites, such as for Apodiformes, a tropical nectar-feeding in their natural habitat. From August 2012 to May 2014, humminbirds were captured using mist nets, and examined for the presence of nasal mites (identified according to specific keys) in the Pantanal, and Cerrado biomes, from the Mato Grosso state, midwestern Brazil. Overall, 76 Apodiform specimens, from the Trochilidae family were captured, and 20 female nasal mites, identified as being from the Rhinoseius genus, were collected from eight hosts (10.5%), of the following species: Amazilia fimbriata, Amazilia versicolor, Eupetonema macroura, and Thalurania furcata. The Rhinoseius spp. has been reported on, in many ecosystems in the Americas, including Brazil, however, this is the first report on Apodiformes from the Pantanal biome. Phoretic mites are not responsible for direct damage to the population of Apodiformes, as they are not pathogenic. However, they compete for food with hummingbirds and decrease the quantity of food available in the environment. They also affect the reproductive dynamics of plants, feed on pollen, and interfere with the intricacies of the biodiversity where they live.